Vidéos écologistes virales sur YouTube : une analyse contextuelle des supports et des configurations discursives - Florimond Rakotonoelina (MediAzioni)
This article analyzes viral environmentalist videos on YouTube. To do so, it observes the rise of the term “viral video” in the media and examines virality from a lexical point of view. Then, virality is connected with temporality in reference to an epidemiology of cultural representations on one hand, and with the discourse of knowledge transmission, on the other hand. The material characteristics of the corpus are then described, which shows one aspect of the virality of these videos, and the content of popularization and environmentalist discourse and the scenography of these videos are finally explained, which presents another aspect of virality.